The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1177/074823379501100202
|View full text |Cite
|
Sign up to set email alerts
|

Methyl-Tertiary-Butyl Ether (MTBE) — a Gasoline Additive — Causes Testicular and Lympho Haematopoietic Cancers in Rats

Abstract: In the framework of a series of experiments conducted to evaluate the carcinogenic effects of oxygenated gasoline additives, MTBE was analyzed in an oral lifetime carcinogenicity study using 8-week-old male and female Sprague-Dawley rats. These experiments were part of a large research project on gasoline carcinogenicity performed at the Bentivoglio (BT) Castle Cancer Research Center of the Ramazzini Foundation and of the Bologna Institute of Oncology, MTBE, dissolved in oil, was administered by stomach tube a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
146
0
5

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(151 citation statements)
references
References 7 publications
0
146
0
5
Order By: Relevance
“…The main concern however is with its potential adverse human health effects, symptoms of which include headache, cough, nausea dizziness and skin irritation [6]. Reference [7] showed that exposure to MTBE caused an increase in cell tumors, lymphomas and leukemia in rats. The United States Environmental Protection Agency (USEPA) has classified MTBE as a potential human carcinogen and recommended a concentration limit of 20 to 40µg/L in drinking water in order to avoid undesirable odor and taste problems [8].…”
Section: Introductionmentioning
confidence: 99%
“…The main concern however is with its potential adverse human health effects, symptoms of which include headache, cough, nausea dizziness and skin irritation [6]. Reference [7] showed that exposure to MTBE caused an increase in cell tumors, lymphomas and leukemia in rats. The United States Environmental Protection Agency (USEPA) has classified MTBE as a potential human carcinogen and recommended a concentration limit of 20 to 40µg/L in drinking water in order to avoid undesirable odor and taste problems [8].…”
Section: Introductionmentioning
confidence: 99%
“…The higher water solubility and persistence of MTBE can cause it to move faster than many other component of gasoline when released into aquifer. The toxicity of MTBE to animals and humans is well documented and it has been established that the MTBE is carcinogenic to animals (Belpoggi et al, 1995, Kamalan et al, 2009Liang et al, 2010). Franklin (2000) reported that MTBE has become one of the most problematic pollutants in urban soils and groundwater worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…For example, benzene is a human carcinogen; 10 chloroform, 11 dichloromethane, 12 dioxane, 13 and carbon tetrachloride 14 are carcinogenic in experimental animals; and DMF 15 and MTBE 16,17 may be carcinogenic. Organic solvents are, in general, flammable and toxic by inhalation, ingestion, and skin absorption.…”
Section: Working Practicesmentioning
confidence: 99%